Financialization, price risks, and global commodity chains: Distributional implications on cotton sectors in Sub-Saharan Africa - Cornelia Staritz; Susan Newman; Bernhard Tröster; Leonhard Plank (Austrian Foundation for Development Research (ÖFSE), 2015)
The functioning of commodity markets has changed related to processes of financialization that involve two major developments - the rise of financial interest on commodity derivative markets through the increasing presence of financial investors and the changing business models of international commodity trading houses and the increasing importance of these markets in price setting and risk management since the liberalization of national commodity sectors. A critical question is how these global financialization processes affect commodity producers in low income countries via the operational dynamics of global commodity chains and distinct national market structures. This paper investigates how global financialization processes influence how prices are set and transmitted and how risks are distributed and managed in the cotton sectors in Burkina Faso, Mozambique and Tanzania. It concludes that uneven exposure to price instability and access to price risk management have important distributional implications. Whilst international traders have the capacity to deal with price risks through hedging in addition to expanding their profit possibilities through financial activities on commodity derivative markets, local actors in producer countries face the challenge of price instability and increased short-termism - albeit to different extents deepening on local market structures - with limited access to risk management.
Keywords: 330; commodity markets; financialization; global commodity chains; commodity prices; price risks; price risk management; cotton sector; Africa